Response to Mixing Wheat Seed with Fertilizer in the Drill at Planting - C. Weber; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
Mixing dry phosphorus (P) fertilizer with winter wheat seed is common in Kansas to provide a starter fertilizer benefit to the crop. This study was designed to evaluate the effects of dry P sources, rates, and times fertilizer mixed with wheat seed, effects on early growth and overall productivity and yield of the crop. Two winter wheat studies were conducted in the 2018–2019 wheat growing season at Manhattan (site 1) and Topeka (site 2) Kansas. The previous crop for site 1 was soybean and corn at site 2. The winter wheat was no-till drilled at 70 lb/a and mixed with either diammonium phosphate (DAP) (18-46-0) or Micro-Essentials SZ “MESZ” (12-40-0-10S-1Zn) rates of 30, 60, and 120 lb P2O5/a. Mixing times in which wheat seed was in contact with the fertilizer were 0, 12, 28, and 40 days. The winter wheat was drilled in October and November and top-dressed with 100 lb N/a using UAN 28% at green-up in the spring. The overall trends observed in these preliminary results suggest that either P fertilizer source can be stored for a prolonged period of time with no negative impact, and producers can avoid the economic expenses of replacing the seed-fertilizer blend.
Keywords: wheat; phosphorus; fertilizer; seed; planting